As luzes e os sons madrigalescos de um Botelho innamorato - Coelho, Daniella Bibi Paez (2018)
This work aims to present an analytical panorama of the twenty-three madrigals in Portuguese language, constant in the multilingual work Musica do Parnasso (1705), by Manuel Botelho de Oliveira (Salvador, 1636-1711), under the point of view of the acute construction. For this, in the first chapter we present a brief biographical excursus and the appreciation of the work and the critical fortune of the author, letting know and commenting the prologue of a manuscript work, until then unpublished, Jardim historial de conceituosas flores (1704), which updates his own bibliography. In the second chapter, we discuss some fundamental theoretical points for the study of corpus in question: the difficult definition of the lyrical genres and the primacy of the loving themes; the relation of poetry with rhetoric; the practice of engenho and agudeza; the specific case of madrigal in the treatises of poetry of the time and its relation with music. In the third chapter, we weave a general comment about the forty-eight madrigals (in Portuguese, Castilian and Italian) composed by the author, presenting elocutory similarities, and we proceed to the analysis of twenty-three madrigals in Portuguese language, divided in semantic axes, emphasizing the rhetorical procedures, in order to extract the metaphorical lights and the sounds of the madrigals by Botelho and from them present a panorama. Likewise, once that in Musica do Parnasso many poems are in honor to Anarda and from this fictional beloved celebrate the beauty and the rigors, we propose, also, the thesis that from her composes an etopeia, that is, a physical and moral portrait, and, since the madrigals analyzed integrate this honor, from this thesis make equally proof.